VIEWS OF FOREIGN STUDENTS LEARNING TURKISH ON TURKISH INSTRUCTORS - Ogur, Erol; Baştürk, Şükrü; Gültekin, Filiz; Şahin, Şenay (International Online Journal of Education and Teaching, 2023)
In language teaching, in addition to the curriculum, the use of equipment, the attitudes and views of the instructor/educators and students about one another have a significance of its own. In an attempt to identify and examine the students’ views on Turkish instructors in the process of teaching Turkish as a foreign language, this study aimed to reveal the relationship between the views of foreign students learning Turkish in Turkey on their instructors, in terms of gender, age and education level by using the relational scanning design. The data were collected from a total of 415 students who came to the Turkish Teaching Implementation and Research Center (ULUTÖMER) of Bursa Uludağ University in order to learn Turkish in the spring semester of 2020-2021. A triple point questionnaire consisting of 39 items was utilized to identify the views of foreign students towards their instructors. The questionnaire consisted of items related to the interaction of the students with their instructors, the cultural sensitivity of the instructors, the classroom management aa well as the teaching skills of the instructors. Before the questionnaire items were applied, they were presented to the expert opinion and the questionnaire items were finalized in accordance with the feedback of the experts. Participants were informed about the study and the link of the questionnaire form was shared with them. For the analysis of the data, a descriptive analysis was performed for the variables of age, gender and education level. The frequencies and percentages of the answers given by the participants to the questions were established and the χ2 (chi-square) test was carried out to identify whether there was a significant relationship between the responses of the participants in terms of gender, age and education level. Cramer’s V coefficient was utilized to calculate the strength of the relationship between the variables in the chi-square test used. In the statistical analyzes used in the study, the level of significance was accepted as 0.05.